Comparison of Studentsâ Characteristics, Self-Motivation, and Readiness of Self-Directed Learning Implementation among Medical Students at Maranatha Christian University - Gunanegara, Rimonta F; Wahid, Mardiastuti H; Widyahening, Indah S (Journal of Medicine and Health, 2017)
Self-Directed Learning (SDL) is an important skill that must be achieved by medical students.The aim of this study is to identify the level of self-motivation and SDL readiness in the medicalstudents as well as to identify factors affecting SDL. This is is a mixed method research,involving first-year and clinical year medical students. A quantitative research is conducted bydistributing self-motivation (MSLQ) and SDL questionnaire (SDLRS). A total sampling isapplied to select the respondents. Furthermore, focus group discussion (FGD) on students andtutors/preceptors is carried out. Informants are chosen by purposive sampling method. Thisresearch reveals that most of medical students have a good level of self-motivation but a lowlevel of SDL readiness. Nevertheless, the mean scores of SDL readiness in both groups showsno significant differences. The research also identifies four major factors affecting the SDLreadiness, namely the studentsâ characteristics, learning process, the role of tutors/preceptorsand supporting facilities for learning. There is no significant difference between SDL readinessof the first-year and clinical year of medical students. Unprepared studentsâ characteristics,sub-optimal learning process, unsupported role of tutors/preceptors and inadequate learningresources are found to be the mayor factors influencing SDL readiness.Keywords: self-directed learning readiness; self-motivation; problem-based learning